Wild-Type MIC Distributions and Epidemiological Cutoff Values for Caspofungin and Aspergillus spp. for the CLSI Broth Microdilution Method (M38-A2 Document) - Espinel-Ingroff, A. (American Society for Microbiology, 2011)
Clinical breakpoints have not been established for mold testing. Epidemiologic cutoff values (ECVs) are available for six Aspergillus spp. and the triazoles, but not for caspofungin. Wild-type (WT) minimal effective concentration (MEC) distributions (organisms in a species-drug combination with no acquired resistance mechanisms) were defined in order to establish ECVs for six Aspergillus spp. and caspofungin. The number of available isolates was as follows: 1,691 A. fumigatus, 432 A. flavus, 192 A. nidulans, 440 A. niger, 385 A. terreus, and 75 A. versicolor isolates. CLSI broth microdilution MEC data gathered in five independent laboratories in Canada, Europe, and the United States were aggregated for the analyses. ECVs expressed in μg/ml that captured 95% and 99% of the modeled wild-type population were for A. fumigatus 0.5 and 1, A. flavus 0.25 and 0.5, A. nidulans 0.5 and 0.5, A. niger 0.25 and 0.25, A. terreus 0.25 and 0.5, and A. versicolor 0.25 and 0.5. Although caspofungin ECVs are not designed to predict the outcome of therapy, they may aid in the detection of strains with reduced antifungal susceptibility to this agent and acquired resistance mechanisms.